OPTIMALISASI PENJUALAN TANAMAN PLATYCERIUM PADA UMKM PONDOKTANMAN MELALUI SISTEM E-COMMERCE BERBASIS WEB - Ni Made Sokayani; I Nyoman Yudi Anggara Wijaya; Putu Trisna Hady Permana (INFOTECH journal, 2025)
UMKM Pondoktanman is abusiness engaged in the sale of ornamental plants, especially Platycerium plants. However, the sales process that is still carried out manually causes several obstacles, such as the difficulty of managing order data, inefficient transaction recording, and limited market reach. To overcome these problems,a website-based sales information system is needed that can help simplify sales process and manage data effectively and efficiently. This study aims to design a website-based Platycerium plant sales information system using the Extreme Programming ( XP ) Method. The XP Method was chosen because it is able to accommodate system needs quickly through aniterative and flexible development cycle. The XP stages including planning, design, coding, and testing are implemented in a structured manner to ensure that the system developed is in accordance with user needs. The results of this study are a website-based sales information system that has main features such as product catalogs, shopping carts, order management, and sales reports. This system is expected to be able to increase the efficiency of the sales process, expand market reach, and provide aneasier shopping experience for customers.